Case Study Implementation of Reasonable Accomodations for Students with Special Needs at SMPN 32 Kota Tangerang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the implementation of reasonable accommodations for students with special needs at SMP Negeri 32 Kota Tangerang. The research focuses on how inclusive education is operationalized within a public junior high school context to ensure equal educational opportunities for all learners, regardless of their physical, intellectual, or emotional differences. The central problem addressed concerns the extent to which inclusive policies and practices are effectively translated into tangible support systems for students with special needs. Accordingly, the primary objective of this study is to analyze the implementation process, challenges, and outcomes of reasonable accommodations in promoting inclusive learning environments. A qualitative research design was employed, utilizing data collection techniques such as observation, in-depth interviews with the principal, special education teachers, homeroom and subject teachers, as well as students with special needs, complemented by documentation analysis. The validity of the data was established through triangulation, encompassing processes of data reduction, data display, and conclusion drawing. The findings demonstrate that SMP Negeri 32 Kota Tangerang has successfully implemented reasonable accommodations supported by the BOSDA Inklusi program. This funding facilitates the provision of accessibility features—including ramps, guiding blocks, accessible toilets, and wheelchairs—alongside adaptive learning materials and teacher remuneration. Furthermore, systematic identification and assessment procedures are conducted regularly, and the curriculum is continuously adapted to meet individual learning needs. The school also organizes regular capacity-building programs for educators and staff. In addition, strong collaboration with the Tangerang City Government, the Difabel Mandiri Indonesia Foundation, and USAID Madani provides sustained technical assistance and monitoring.